Aktivitas Antioksidan Ekstrak Etanol U Groh (Cocos nucifera L.) dengan Metode DPPH - Misrahanum Misrahanum; Nurul Alfiyani; Murniana Murniana (Journal of Pharmaceutical and Sciences, 2023)
U groh shells and coir (Cocos nucifera L) have the potential as antioxidants. This study aimed to evaluate the IC50 value of young coconut ethanol extract as an antioxidant. The DPPH technique was used for extraction and antioxidant activity testing at concentrations of 6.25;12.5; 25; 50, and 100 ppm. The ethanol extracts of young coconut shell and coir generated antioxidant activity with IC50 values of 11.811 ppm and 42.483 ppm, respectively, and were classified as very active (50 ppm). As a result, young coconut shells and coir can be used as an antioxidant source.